An analysis of the strategic, operational, and organizational differences between the Islamic State and al-Qa'ida - Greene, Jacob (AUC Knowledge Fountain, 2014)
This project provides a comprehensive examination of the strategic, operational and organizational character of the Islamic State in Iraq and the Sham (ISIS). The purpose of the project is two fold: first, to challenge the perception that ISIS and al-Qā’ida are fundamentally “one and the same;” and, second, to offer policy makers a systematic and detailed description of ISIS on its own merits. Drawing on variables pertaining to three dimensions—strategy, operations, and organizational characteristics—and informed by both primary sources and secondary analyses, I investigate the qualitative differences between the two organizations. I find that, despite some similarities, ISIS and al-Qā’ida vary considerably in all facets. Accordingly, I offer targeted policy recommendations aimed at making current counter-strategy more effective and efficient.